Արևմտյան Հայաստանի Երզնկա և Էրզրում քաղաքների նկարագրությունը գերմանացի ուղեգիրների աշխատություններում - Շախկյան, Գայանե («Նաիրի» հրատ.)
Many German travelers have visited both Eastern and Western Armenia in the 19th century to conduct researches there. In the mentioned period Armenia was under the rule of the Ottoman Empire. The economic and social hard conditions of Armenian people were drawing the attention of foreign authors for years.
Keywords: Ուղեգրություն; Արևմտյան Հայաստան